A case of genetic polyandry in the shortfin mako Isurus oxyrinchus. Issue 3 (28th July 2015) - Corrigan, S.; Kacev, D.; Werry, J.
<x xml:space="preserve">Abstract</x> This article documents a case of genetic polyandry in the oceanic and pelagic shortfin mako Isurus oxyrinchus and briefly comments on the implications of this finding.